Scientific Applications of Grid Computing First International Workshop, SAG 2004, Beijing, China, September, Revised Selected and Invited Papers - Pérez, Maria S.; Robles, Victor (Theoretical Computer Science and General Issues, 2005)
We wish to extend a warm welcome to the reader of this extended postp- ceedings publication of SAG 2004, the 1st International Workshop on Scienti?c Applications on Grid Computing. This workshop was held in September 2004, in conjunction with the 2004 IEEE/WIC/ACM International Joint Conference on Web Intelligence (WI 2004) and Intelligent Agent Technology (IAT 2004). The WI and IAT conferences have provided, for several years, a leading - ternational forum to bring together researchers and practitioners from diverse ?elds,suchascomputerscience,informationtechnology,business,education,- man factors, systems engineering, and robotics, to explore the fundamental roles as well as practical impacts of arti?cial intelligence (AI) (e.g., knowledge r- resentation, planning, knowledge discovery, and data mining, intelligent agents and social network intelligence) and advanced information technology (IT) (e.g., wireless networks, ubiquitous devices, social networks, the Wisdom Web, and data/knowledge grids), and to examine the design principles and performance characteristics of various approaches in intelligent agent technology.